2006
DOI: 10.1089/acm.2006.12.673
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese Medicine Treatment of Epilepsy

Abstract: Decrease of seizure frequency and severity in three epileptic patients was achieved by adding Bu-yang-huan-wu-tang to conventional therapy according to the principles of Traditional Chinese Medicine (TCM) theory. This treatment mainly relied on the resolution of blood stagnation in cerebrovascular systems. Blood stagnation is an important underlying pathology of many disease processes according to TCM theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…Patients Suffering from Intractable Diseases Treated Effectively with Medicines of Kampo and TCM http://dx.doi.org/10.5772/60573 81 improvement in the frequency and severity of seizures. This treatment will rely on the resolution of blood stagnation in cerebrovascular systems [36].…”
Section: Prescriptionsmentioning
confidence: 99%
“…Patients Suffering from Intractable Diseases Treated Effectively with Medicines of Kampo and TCM http://dx.doi.org/10.5772/60573 81 improvement in the frequency and severity of seizures. This treatment will rely on the resolution of blood stagnation in cerebrovascular systems [36].…”
Section: Prescriptionsmentioning
confidence: 99%
“…Only one clinical epilepsy study of an herbal extract has been published since 2005 in the English literature. 54 …”
Section: Herbal Therapies For Epilepsymentioning
confidence: 99%
“…Hijikata et al [34] reported on three cases in which patients with refractory epilepsy showed substantial improvement with the use of the traditional herbal formulation Bu-yang-huan-wu-tang. Tyagi and Delanty [24] cited several compelling open-label studies of Chinese herbal remedies, including Qingyangsen and Zhenxianling, suggesting that these medications may have anticonvulsant effects, with fewer side effects than standard antiepileptic drugs.…”
Section: Herbal Remediesmentioning
confidence: 99%